PENGARUH LABA BERSIH, ARUS KAS OPERASI, DAN ARUS KAS BEBAS TERHADAP PEMBAYARAN DEVIDEN KAS PADA PERUSAHAAN KONTRUKSI BANGUNAN YANG TERDAFTAR DI BEI TAHUN 2016-2019 - Raja Ade Fitrasari Mochtar,; Siska,; Samsu Rizal Putratama, (Journal Of Islamic Finance And Accounting Research, 2022)
The purpose of this study was to determine the effect of net income, operating cash flow and free cash flow on cash dividends in building construction companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019 partially or simultaneously. This research uses quantitative methods and uses secondary data sources. The population in this study is the building construction sub-sector companies listed on the IDX in 2016-2019. The method used in sampling is purposive sampling, so that through this method, there are 10 companies as samples from the total population of 16 companies.This study uses data analysis techniques consisting of descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing on SPSS version 26. The results of this study prove that partially there is a significant effect of net income on cash dividends, while operating cash flows and cash flows Free cash each partially has no significant effect on cash dividends. Meanwhile, simultaneously net income, operating cash flow, free cash flow have a significant effect on cash dividends.